The FORCE Metaphor in Conceptualizing Economic Recession - Cibulskienė, Jurga (Respectus Philologicus, 2013)
Cognitive metaphor analysts comprehend metaphor as a convenient way of not only talking about real life events but also thinking about them: connecting ideas, explaining abstract ideas that are difficult to grasp, conveying messages and emotions, etc. Thus, metaphor in real-world discourse is increasingly becoming the focus of many cognitive studies. In political discourse, metaphor is seen as an ideological tool of deliberate attempts to influence, persuade and manipulate people. As Charteris-Black (2005: 16) put it, politicians try to establish themselves in a positive light or legitimize themselves, i.e., by presenting evidence that they are charismatic leaders who are capable of running their country efficiently. Legitimization goes hand in hand with delegitimization, i.e., negative other-presentation. Metaphor as a cognitive mechanism of ideology may serve both as positive self-representation and as a tool for fault-finding in others. Thus, the study focuses on how three Lithuanian socio-political groups (the leading party, the opposition, and the media) legitimize themselves and delegitimize their opponents by using force metaphors to conceptualize the worldwide economic recession. The findings indicate that although the same conceptual metaphor is used for legitimization and delegitimization, its fulfilment scenario appears to be markedly different and it carries different rhetorical implications in the three discourses.
Keywords: Economic Recession; Critical Metaphor Analysis (CMA); Force Metaphor; Legitimization; Delegitimization